Realizing smart microgrid electricity solutions for rural communities using a hybrid microgrid system based on renewable energy sources - Jabbar, Murtadha Hameed; Abdullah, Ahmed Kareem; Ali, Faris Mohammed (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Hybrid renewable energy sources are combined in microgrids to feed rural areas and remote locations where grid power is unavailable. This study aims to feed remote areas and newly established projects or factories far from the power source using renewable energy sources to continuously satisfy various load demands and supply power. A smart microgrid design is proposed for a hybrid system that includes solar energy with an artificial neural network (ANN), a wind turbine, an energy storage system that stores energy in a photovoltaic battery and uses it when needed, and an emergency diesel generator. To verify the effectiveness of the proposed approach, a mobile generation station consisting of diesel generators, solar PV systems, wind turbines and an energy storage system that stores energy in a bank of batteries is designed as an additional service source in MATLAB Simulink. The model has a capacity of 1MW and can handle loads of up to 800KW. With ANN, a stable output voltage solar without ripples was obtained. Load priority algorithm (LPA) was also used to coordinate between three loads: High, Medium, and Low Load priority, and the actual diamond for each load was achieved. The first load with the highest priority was fed 100 %, and the remaining loads were fed to cover their needs, proving the design’s validity. It demonstrates the effectiveness of the proposed solution in mitigating power outages. The station can serve all loads by using renewable energy sources (RES) to meet the energy demands of the loads